2014
DOI: 10.1007/s13277-014-2062-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel p53 codon 240 Ser > Thr coding region mutation in the patients of oral squamous cell carcinoma (OSCC)

Abstract: Chewing habits of tobacco, betel quid (paan), and betel nut (chhaliya) are common traditions in Pakistan. Different other preparations and combination of flavors with tobacco, paan, and chhaliya ingredients are commonly available in the market and have received considerable attention as sources of carcinogens that promote OSCC. Mutagens can damage DNA and generate promutagenic lesions. The germ line mutation/polymorphism of p53 gene has been reported to be involved in multiple steps of carcinogenesis. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Recently, Saleem et al analyzed loss of function mutations in p53 gene in the patients of oral squamous cell carcinoma and found that AGT to ACT missense mutation in DNA binding domain may result in impaired p53 function. In chronic lymphocytic leukemia patients, missense mutations in DNA binding motif were correlated with poor survival [154,155]. p53 has been considered as a significant player of apoptosis in many studies, and there is a growing accumulation of articles revealing its role in many malignancies.…”
Section: Death Receptormentioning
confidence: 99%
“…Recently, Saleem et al analyzed loss of function mutations in p53 gene in the patients of oral squamous cell carcinoma and found that AGT to ACT missense mutation in DNA binding domain may result in impaired p53 function. In chronic lymphocytic leukemia patients, missense mutations in DNA binding motif were correlated with poor survival [154,155]. p53 has been considered as a significant player of apoptosis in many studies, and there is a growing accumulation of articles revealing its role in many malignancies.…”
Section: Death Receptormentioning
confidence: 99%
“…The oxidative stress and subsequent ROS generation leads to cell proliferation, ended into tumorigenesis depending upon the degree of ROS production. A continual exposure to such carcinogens can result in lesions in the oral cavity and consequently end into cancer .…”
Section: Introductionmentioning
confidence: 99%
“…1A ). In addition, a new mutation in exon 7 of the p53 gene has been identified in the tumors of patients with oral squamous cell carcinoma (OSCC) ( 15 ). A missense mutation resulting in a codon alteration from ‘AGT’ to ‘ACT’ was identified at position 719 of TP53 ( 15 ).…”
Section: P53 Mutations In Hnsccmentioning
confidence: 99%